2017
DOI: 10.1002/car.2475
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Corporal Punishment among Creole and Maroon Professionals and Community Members in Suriname

Abstract: Child discipline is a vital part of child‐rearing in all cultures. The need for child discipline is generally recognised, but considerable debate exists regarding the best methods. Corporal punishment (CP) is a dominant practice in Caribbean cultures. This qualitative study investigated community perceptions of the function, legality and boundaries of CP in child‐rearing practices in Suriname, in which CP is defined as hitting a child on their buttocks or extremities using an open hand. Twelve focus group disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Despite their cultural and linguistic diversity, when it comes to parenting, Surinamese parents have some notable commonalities with those of mothers and fathers in other CARICOM countries. A predominant aspect of parenting across Caribbean countries (e.g., Barbados, Guyana, Jamaica, and Trinidad and Tobago) is the use of a combination of warmth and harshness during childrearing (Griffith & Grolnick, 2014; Roopnarine et al, 2014), and harsh parenting practices in the form of physical punishment and denigration have been documented among Maroons, Creoles, and Hindustanis in Suriname (Marshall & van der Wolf, 2013; van der Kooij et al, 2015, 2017, 2018). The use of harsh parenting not only undermines meaningful cognitive and social engagement with young children in the Caribbean region (Roopnarine et al, 2014), but as in other cultural communities around the world, it has detrimental effects on their social and cognitive development (see Roopnarine & Dede Yildirim, 2019b, for review).…”
mentioning
confidence: 99%
“…Despite their cultural and linguistic diversity, when it comes to parenting, Surinamese parents have some notable commonalities with those of mothers and fathers in other CARICOM countries. A predominant aspect of parenting across Caribbean countries (e.g., Barbados, Guyana, Jamaica, and Trinidad and Tobago) is the use of a combination of warmth and harshness during childrearing (Griffith & Grolnick, 2014; Roopnarine et al, 2014), and harsh parenting practices in the form of physical punishment and denigration have been documented among Maroons, Creoles, and Hindustanis in Suriname (Marshall & van der Wolf, 2013; van der Kooij et al, 2015, 2017, 2018). The use of harsh parenting not only undermines meaningful cognitive and social engagement with young children in the Caribbean region (Roopnarine et al, 2014), but as in other cultural communities around the world, it has detrimental effects on their social and cognitive development (see Roopnarine & Dede Yildirim, 2019b, for review).…”
mentioning
confidence: 99%
“…The basic psychological principles (e.g., parent–child relationship building through play and positive attention, child behavior change through social learning) of a parenting course such as LMP are universal across cultures (O’Connor, Matias, Futh, Tantam, & Scott, 2013). Furthermore, the principles of LMP do not fit only the principles of the CRC (treating children respectfully, setting parenting goals, supporting parents in raising questions, and learning to renounce violence); they also fit local customs and wishes in Suriname, such as requirements for nonviolent strategies and understanding and respect for longstanding habits (van der Kooij et al, 2017). Our program adhered to the imported manual and training methods, with some adaptations for Suriname.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, no other evidence-based programs have been implemented, adapted, and evaluated. A recent study on CP among Creoles and Maroons conducted in Suriname showed that both adults and adolescents believed that using some form of CP is at times a necessary and a respected form of child discipline (van der Kooij et al, 2017). Those who received CP agreed on the necessity or acceptability of CP when this was “in the best interest of the child” and did not consider CP as a form of violence or maltreatment in that case.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It leaves us, firstly, with the view that cultural knowledge is of the utmost importance to make decisions about the transferability of models (Walker-Simpson, 2017). Secondly, it seems as if governments should be aware of cultural context in child protection to ensure culturally appropriate reforms, policy and legislation (Lin, 2017;van der Kooij et al, 2017), as even corporal punishment seems to be more related to culture and context than other socio-economic factors (Ellonen et al, 2017). Lastly, pilot studies where a participatory action research approach is adopted could be useful (Walker-Simpson, 2017) to promote culturally acceptable child protection outcomes.…”
mentioning
confidence: 99%